Handbag de Mark Ravenhill (1998) : réincarnation de The Importance of Being Earnest à la fin des années 1990 - Xavier Giudicelli (Cahiers Victoriens et Edouardiens)
What is often stressed about The Importance of Being Earnest is its verbal quality. This article focuses on a version of The Importance of Being Earnest which, paradoxically, brings the body centre-stage. The play Handbag by Mark Ravenhill (one of the quintessential writers of so-called “in-yer-face” theatre), first produced at the Lyric Theatre, Hammersmith, in 1998, is a rewriting of The Importance of Being Earnest which shifts the emphasis from the verbal to the physical. This article first replaces Handbag in its political, aesthetic and critical contexts: the emergence of “in-yer-face” theatre in the 1990s, Wilde as a key figure in gay studies and queer theory in the late-1980s and 1990s in the United States and in Great Britain (with the works of E.K. Sedgwick, Jonathan Dollimore and Alan Sinfield). It then examines the adaptation strategies used by Ravenhill in his reprising of The Importance of Being Earnest. Handbag reads both as a transposition and an explicitation of Wilde’s play. It is built around two plots which parallel and intersect each other: one revolves around a lesbian couple and a gay couple having a baby, the other involves a set of Victorian characters and stages a “prequel” of Wilde’s play. Besides, the coded allusions to Bunburying or eating cucumber sandwiches are explicitated in Ravenhill’s version. Handbag thus creates a dialogue between past and present and raises questions about our current society’s relationship to the Victorians.